The Effect of Promotion, E-Service Quality and Price on Customer Satisfaction and Its Implication on Loyalty of Tokopedia Customers - Frans Sudirjo; Vivid Violin; Akmal Abdullah; Ifadhila; Muhammad Subhan Iswahyudi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study examined how consumer happiness and customer loyalty are affected by the quality of e-services, product prices, and promotions. This study aims to identify if a variable has a direct or indirect impact. A questionnaire with 40 questions that was sent using Google Form was used to gather the data for this investigation. A non-probability selection technique was used to select 100 participants as respondents for this investigation. Path analysis utilizing statistical product and service solutions (SPSS) is the analysis method used in this study. According to the study's findings, client loyalty and partial and simultaneous effects of e-service quality and promotion on customer satisfaction are both favorable. Customer loyalty is impacted by product prices, which also have a detrimental impact on customer satisfaction. Customer loyalty is indirectly impacted by consumer happiness, which is influenced by e-service quality, product prices, and incentives.